Merging perspectives: genotype‐directed molecular therapy for hereditary diffuse gastric cancer (HDGC) and E‐cadherin–EGFR crosstalk. Issue 1 (22nd February 2018) - Li, Dandan; Lo, Winifred; Rudloff, Udo
Abstract: Hereditary diffuse gastric cancer is a cancer predisposition syndrome associated with germline mutations of the E‐cadherin gene (CDH1; NM_004360). Male CDH1 germline mutation carriers have by the age of 80 years an estimated 70% cumulative incidence of gastric cancer, females of 56% for gastric and of 42% for lobular breast cancer. Metastatic HDGC has a poor prognosis which is worse than for sporadic gastric cancer. To date, there have been no treatment options described tailored to this molecular subtype of gastric cancer. Here we review recent differential drug screening and gene expression results in c.1380del CDH1‐mutant HDGC cells which identified drug classes targeting PI3K (phosphoinositide 3‐kinase), MEK (mitogen‐activated protein kinase), FAK (focal adhesion kinase), PKC (protein kinase C), and TOPO2 (topoisomerase II) as selectively more effective in cells with defective CDH1 function. ERK1‐ERK2 (extracellular signal regulated kinase) signaling measured as top enriched network in c.1380delA CDH1‐mutant cells. We compared these findings to synthetic lethality and pharmacological screening results in isogenic CDH1 −/− MCF10A mammary epithelial cells with and without CDH1 expression and current knowledge of E‐cadherin/catenin–EGFR cross‐talk, and suggest different rationales how loss of E‐cadherin function activates PI3K, mTOR, EGFR, or FAK signaling. These leads represent molecularly selected treatment options tailored to the treatment of CDH1‐deficient familial gastric cancer.